Christians Facing the Challenge of Poverty: The Case of FJKM Ambohidavenona Lovasoa - Tsimy, Andriantsilaniarivo; Baholy, Robijaona Rahelivololoniaina (Budapest International Research and Critics University, 2025)
This article talks about poverty and Christian commitments in the face of it. This article is important because it brings a new practice to fight poverty. It’s destiny for political and theologian who emit the politic of developpement. Poverty is a situation caused by the destabilization of society. The poor are sometimes victims of oppression and injustice. This situation can affect anyone, even Christians. But God created man to live in good situation and prosperity. He wants to lift man out of poverty. Indeed, the theme of this article is: Christians and the challenge of poverty in the case of Ambohidavenona. To address this subject, it is essential to know the aspect of poverty in this environment, as well as the Christian commitment to face it. Even though the initiatives and actions of the church, the Christians of Ambohidavenona still live in general, economic, social and spiritual poverty. Overcoming poverty is truly God's plan. It would then be appropriate to improve the attitude of the rich towards the poor, consolidate Christian solidarity, intensify work as a source of income and, above all, strengthen faith in God. So the practice of theology of liberation, based on Christian commitment to the poor.